The performance of open-end Brazilian fixed income mutual funds for retail clients - Weintraub, Abraham Bragança de Vasconcellos (2013)
From a financial perspective, this dissertation analyzes the Brazilian mutual fund industry performance for an average retail client. The most representative funds for the local population, that are the fixed income open-end ones, will be selected and their performance will be measured aiming to answer if clients of this industry obtained a proper return over their investments in the period between August 2010 and August 2013. A proper return will be understood as the preservation of the purchasing power of the individual´s savings, what is achieved with a positive performance of a mutual fund after discounting taxes, administrative fees and inflation. After obtaining an answer for the previous question, this dissertation will explore a possible alternative solution: Tesouro Direto, that is an example of a financial approach that could foster the disintermediation between savings and investments through electronic channels. New electronic platforms, with a broader scope, could be utilized to increase the efficiency of funding productive investments through better remunerating Brazilian savings. Tesouro Direto may point towards a new paradigm.